2016
DOI: 10.1007/s00277-016-2795-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypoalbuminemia is significantly associated with increased clearance time of high dose methotrexate in patients being treated for lymphoma or leukemia

Abstract: As a weak acid, methotrexate (MTX) is bound to serum albumin and has variable protein binding. The purpose of this study was to assess serum albumin’s relationship with MTX pharmacokinetics by comparing MTX clearance and toxicities between patients with normal serum albumin to those with hypoalbuminemia. This single-center retrospective study included adult patients with leukemia or lymphoma who received their first MTX at a dose ≥ 1 gram/m2. Hypoalbuminemia was defined as serum albumin ≤ 3.4 g/dL. MTX clearan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 18 publications
1
39
2
Order By: Relevance
“…MTX is a week acid and binds to serum albumin. Reiss et al have shown that hypoalbuminemia is associated with decreased MTX clearance and an increased length of hospitalization [28]. In our patients, however, the 48 h MTX plasma levels and length of hospitalization did not differ in the patients with and without hypoalbuminemia.…”
Section: Discussioncontrasting
confidence: 75%
“…MTX is a week acid and binds to serum albumin. Reiss et al have shown that hypoalbuminemia is associated with decreased MTX clearance and an increased length of hospitalization [28]. In our patients, however, the 48 h MTX plasma levels and length of hospitalization did not differ in the patients with and without hypoalbuminemia.…”
Section: Discussioncontrasting
confidence: 75%
“…Additionally, the NOPHO database had limited covariates to explore. There is considerable interindividual variability in MTX clearance that previous publications have demonstrated to be partially explained by serum albumin, 42 creatinine clearance, 40,43 estimated glomerular filtration rate, 28 concomitant medications, 44 and SLCO1B1 genotype. 18,41,45,46 Furthermore, our PK data did not include information regarding aspects of supportive care, like fluid hydration and urine pH, which can impact MTX clearance.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 40 Hypoalbuminemia can increase the clearance time of HDMTX, leading to hyperbilirubinemia and prolonged hospitalization. 41 Lack of facilities for methotrexate level monitoring, high infection rates, underlying malnutrition, and inadequate supportive care facilities make it difficult to administer HDMTX to most of the patients with osteosarcoma in India and other LMICs. In addition, the costs of a protocol incorporating HDMTX are much higher compared with our protocol (Data Supplement).…”
Section: Discussionmentioning
confidence: 99%